Synthesis of Zeolite from Fly Ash and Bottom Ash and Application for Biodiesel Transesterification - Rika Putri; Fadjar Goembira; Maria Ulfah; Muhammad Andrifar; Rati Yuliarningsih; Rizki Aziz (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Burning coal in a Coal-Fired Power Plant produces by-products like fly ash and bottom ash. Zeolite synthesized from the ash in Teluk Sirih Coal-Fired Power Plant was applied as a catalyst in the biodiesel transesterification reaction. Zeolite synthesis used the hydrothermal method with acid pretreatment. The operating conditions for fly ash zeolite are a 2.4-molar ratio SiO2/Al2O3 and a crystallization time of 6 hours. The bottom ash zeolite used a 2.0-molar ratio SiO2/Al2O3 and a crystallization time of 8 hours. The performance test of the synthesized catalyst was carried out in the transesterification reaction using waste cooking oil as a raw material with a free fatty acid content of 0.7%. The synthesized catalyst was characterized using x-ray diffraction, scanning electron microscope, and Bruneuer-emmet-teller. The biodiesel with the highest yield was analyzed based on SNI 7182: 2015. The synthesis results of the catalyst produced type A zeolite, shown by the typical X-ray diffraction pattern and supported by the morphological test results using a cube-shaped. The surface area of zeolite fly ash and bottom ash is 12.87 m2/g and 5.13 m2/g. The test showed fly ash zeolite had the highest biodiesel yield of 89.66%. Based on the characterization using SNI 7182: 2015, the color and free glycerol met the standards, while density 40 ˚C, kinematic viscosity 40 ˚C, acid number, total glycerol, methyl ester content, and water content did not meet the standards.